2013
DOI: 10.1080/13504851.2013.818205
|View full text |Cite
|
Sign up to set email alerts
|

Health status and time allocation in Spain

Abstract: This article analyses the relationship between health status and the time devoted to both market and nonmarket work by individuals responding to the Spanish Time Use Survey 2002-2003. We find that better health of individuals is associated with an increase in the hours of market work, while reducing the time devoted to nonmarket work. We show that OLS estimations yield biased results, and the use of instrumental variables (IV) is needed to deal with endogeneity issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Those who enjoy their work will downplay their health problems and work longer, while those who dislike their work may exaggerate health problems and retire sooner. Several studies have confirmed the endogeneity of self-reported health measures (Chirikos and Nestel, 1984;Anderson and Burkhauser, 1985;Bazzoli, 1985;Bound, 1991;Haveman et al 1994;Gimenez-Nadal and Ortega, 2013).…”
Section: Data Variables and Descriptive Evidencementioning
confidence: 96%
See 3 more Smart Citations
“…Those who enjoy their work will downplay their health problems and work longer, while those who dislike their work may exaggerate health problems and retire sooner. Several studies have confirmed the endogeneity of self-reported health measures (Chirikos and Nestel, 1984;Anderson and Burkhauser, 1985;Bazzoli, 1985;Bound, 1991;Haveman et al 1994;Gimenez-Nadal and Ortega, 2013).…”
Section: Data Variables and Descriptive Evidencementioning
confidence: 96%
“…By examining data from several countries, our work crucially adds to the study of the relationship between health inequality and time allocation decisions, including the most recent work by Podor and Halliday (2012), Ortega (2013), andMolina (2015). Specifically, we are able to improve our understanding of how better self-reported health status relates to market and non-market work activities, leisure, and personal care for workers in European countries.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This unequal distribution of unpaid work is evident even among women who earn signi cantly higher wages than their husbands [16]. There is also extensive literature suggesting that cross-national differences in institutional policies may in uence the gendered patterns of time allocation [18][19][20][21][22], and thus the gendered disparities in health. Whilst this study does not aim to provide further evidence on this aspect, it is important to note that institutional policies play a role in determining the time-speci c allocation of men and women by either increasing or decreasing the cost and time devoted to unpaid housework, childcare and paid work [12,13,24].…”
Section: Introductionmentioning
confidence: 99%